Artemis Fawl : The arctic incident - Colfer, Eoin, 1965- (London : Puffin, 2003)
Thirteen-year-old criminal mastermind Artemis Fowl must join forces with his nemesis, Captain Holly Short of the Leprechaun fairy police, in order to save his father, one of the few people in the world Artemis loves, who has been kidnapped by the Russian Mafia.
Keywords: Fairies -- Juvenile fiction; Fowl, Artemis (Fictitious character) -- Juvenile fiction; Kidnapping -- Juvenile fiction; Magic -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Fairies -- Fiction; Fantasy; Fowl, Artemis (Fictitious character) -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; Russian language materials; England -- Juvenile fiction; England -- Fiction; Fantastic fiction